2019
DOI: 10.1109/jphot.2019.2898981
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Absorber With Reconfigurable Bandwidth Based on Isotropic Vanadium Dioxide Metasurfaces

Abstract: The design of a broadband tunable absorber is proposed based on a thin vanadium dioxide metasurface, which is composed of a simple array of vanadium dioxide and a bottom gold film. When the conductivity of vanadium dioxide is equal to 2000 −1 cm −1 , simulated absorptance exceeds 90% with 71% bandwidth from 0.47 to 0.99 THz and full width at half maximum is 98% from 0.354 to 1.036 THz with center frequency of 0.695 THz. Simulated results show that absorptance peak can be tuned from 5% to 100% when the conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 33 publications
0
27
2
Order By: Relevance
“…In this study, the TM wave is used for analyses because as demonstrated surface plasmon polaritons and magnetic polaritons could only be excited when the magnetic field is in the y direction. These resonances are solely or altogether coupled resulting in enhancing the absorption of structures [22][23][24]28,29]. The Ag base below the grating is assumed to be thick enough as an opaque, and accordingly, the transmittance is equal to 0, and the absorptance (α) can be computed from one minus the reflectance (R), α = 1 -R, where the reflectance was calculated by the rigorous coupled-wave analysis (RCWA) based on MatLab programming [30].…”
Section: Theoretical Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the TM wave is used for analyses because as demonstrated surface plasmon polaritons and magnetic polaritons could only be excited when the magnetic field is in the y direction. These resonances are solely or altogether coupled resulting in enhancing the absorption of structures [22][23][24]28,29]. The Ag base below the grating is assumed to be thick enough as an opaque, and accordingly, the transmittance is equal to 0, and the absorptance (α) can be computed from one minus the reflectance (R), α = 1 -R, where the reflectance was calculated by the rigorous coupled-wave analysis (RCWA) based on MatLab programming [30].…”
Section: Theoretical Descriptionmentioning
confidence: 99%
“…The enhancement was theoretically and experimentally demonstrated due to such phenomena of surface plasmon polaritons, magnetic polaritons, Fano resonance, or cavity resonance [13][14][15][16][17][18][19][20][21][22][23]. Recently, various single-frequency perfect absorbers working in gigahertz, terahertz, and infrared (IR) ranges have been actively investigated due to their various applications such as IR detectors, bio/chemical sensing, IR imaging devices, thermo bolometers, and so forth [24][25][26][27][28][29][30][31][32]. To be detailed, IR perfect absorbers were constructed based on one dimensional (1D) or 2D multiple layered structures comprising a top metamaterial layer, a middle dielectric spacer layer, and a bottom metal reflector or silicon substrate [15][16][17]23,31].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, special attention has been paid to switchable /tunable metamaterial (MM) absorbers due to their flexibility and fabricability in practical applications . Conventional absorbers operate at frequency‐fixed absorption mode once manufactured unless the structure parameters are altered .…”
Section: Introductionmentioning
confidence: 99%
“…Some feasible methods such as thermal control, electrical control, and optical control have been proposed to realize switchable or tunable absorbers according to respective requirements. Related to these methods, semiconductor materials, graphene, and some phase‐change materials, such as germanium antimony telluride (GST) and vanadium dioxide (VO 2 ), have become important choices for realization of switchable /tunable devices . By incorporating these materials in the resonators, one can regulate the resonance characteristics through adjusting the conductivity of these materials by temperature, bias voltage, or optical power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation